United they stand, divided they fall : the management of multi-sports clubs in New Zealand : a thesis presented in partial fulfilment of the requirements for the degree of Masters in Business Studies in Marketing at Massey University - Galvin, Caroline (Massey University, 2002)
The purpose of this research was to examine the operation of three multi-sports clubs (urban, provincial and rural) to discover the benefits of being associated with a multi-sports club and what factors were critical to the success of multi-sports clubs. A mixed-method case study was employed for this research: face-to-face interviews were conducted with key administrators from three multi-sports clubs, while 211 completed questionnaires were returned from members of these clubs resulting with a 41% response rate. Benefits reported were that multi-sports clubs provide a focus for the community, improve exposure for sponsors, are conducive to developing a family-oriented atmosphere and liberate codes from day-to-day management issues thereby allowing codes to focus on sport development. Factors critical to the success of a multi-sports club include leadership, incorporation of at least one 'strong' code, selecting compatible codes, including both summer and winter codes, ensuring the codes manage their organisation independently to the main committee and hiring facilities to outside groups. Finally, key limitations were that forming a multi-sports club did not necessarily provide more volunteers, that social interaction between codes was not common and that members tended to play only one code in the club. Inequality between codes in a multi-sports club was also addressed, in terms of more attention and money directed at particular codes. The key implications of this study are that codes can emphasise to sponsors the extra exposure they would receive, that multi-sports club should hire out their facilities to maximise their return and that the codes retain their autonomy. Furthermore, such clubs should have at least one strong code to enhance their reputation, ideally include codes played during summer and winter, offer membership discounts to encourage members to play more than one code and promote social interaction by implementing duty teams and weekly prize-givings. These findings and recommendations offer an insight into the operation of multi-sports clubs, and while generalisation cannot be claimed, this study increases the academic knowledge within this area of sport management. Areas of future research include examining how multi-sports clubs are formed rather than managed, to study a multi-sports club in metropolitan area and investigate the operation of multi-sports clubs in pubs.
Keywords: Sports administration; Sport club management; Sports clubs; Multi-sports clubs